The effect of cold -water immersion and passive rest on recovery among sprint athletes / Maisarah Mohd Saleh … [et al.] - Mohd Saleh, Maisarah; Shahudin, Nurul Nadiah; Abd Razak, Fatin Aqilah; Abdul Hamid, Siti Fadhilah; Zakaria, Muhammad Na’imullah (Faculty of Sports Science and Recreation, University Press of Universiti Teknologi MARA, 2020)
Recovery technique could help lessen the fatigue, increased the level of athletes’ fitness and performance. The main purpose of this research was to study the effect of cold - water immersion and passive rest on recovery of performance among sprint athletes. 14 young athletes were selected and have been divided into two groups that was cold- water immersion group (n = 7) and passive rest group (n = 7). Subjects performed three tests; (i) 35meter sprint, (ii) standing broad jump and (iii) sit and reach. Before the athletes did the test, they warm up themselves for 10 minutes. After that, subjects did the recovery techniques which was for 15 minutes and then repeated the tests. Data analysis was analysed using paired samples test which was pre-test and post-test. The results showed that there was significant effect of cold - water immersion on performance, there was significant effect of passive rest on performance and there were significant different on cold - water immersion and passive rest on performance. Cold - water immersion result for 35 meter sprint (p = 0.001), standing broad jump (p = 0.030) and sit and reach (p = 0.002) which was showed the decreased of performance and then for passive rest the result in 35 meter sprint (p = 0.040), standing broad jump (p = 0.042) and sit and reach (p = 0.000) which showed the improvement through cold – water immersion. Implication of this study found that passive rest was good recovery technique for short period of time and cold - water immersion was good for longer period of time.